Structural Failures in an Architectural Heritage Site: Case Study of the Blagoveštenje Monastery Church, Kablar, Serbia - Jelena Ivanović-Šekularac; Neda Sokolović; Nikola Macut; Tijana Žišić; Nenad Šekularac (Buildings)
Authenticity is a core principle in conservation guidelines and a key goal of heritage preservation, especially in Serbia, where many aging objects face ongoing deterioration. The subject of this study is the church within the Blagoveštenje Monastery complex in the Ovčar-Kablar gorge, built using stone from a local quarry at the beginning of the 17th century. The inclination of the structure, observed as progressively increasing over the centuries, raises important concerns regarding its stability. This research focuses on identifying the underlying causes of this phenomenon in order to support its long-term preservation. The methods used the study are long-term in situ observations including analysis, geodetic research, 3D laser imaging, geophysical, geological, archaeological research, evaluation of current condition, determination of structural failures and their cause and monitoring the structural behavior of elements. All methods were carried out in accordance with the definition of rehabilitation measures and the protection of masonry buildings. The main contribution of this study is identifying that the church’s inclination and deviation result from the northern foundation resting on weaker soil and a deeper rock mass compared to the southern side. The research approach and findings presented in this paper can serve as a guide for future endeavors aimed at identifying the causes of deformations and the restoration and structural rehabilitation of masonry buildings as cultural heritage.